The Influence of Service Quality, Price, and Customer Satisfaction on Customer Loyalty of Online Transportation: Study on Maxim Application Service Users in 2025 in Bekasi City - Eddy Suharso (Journal of Management and Social Sciences, 2026)
This study aims to analyze the influence of service quality, price, and customer satisfaction on customer loyalty among Maxim application users in Bekasi City. The problem in this study is motivated by the importance of building customer loyalty amid increasingly competitive online transportation services, evidenced by Maxim's low market share (12.3%) compared to Gojek (54.4%) and a pre-survey showing only 37.5% customer satisfaction. A quantitative approach with purposive sampling technique was employed, collecting data via structured questionnaires using a Likert scale from 111 active Maxim users in Bekasi City during May–June 2025. Data were analyzed using multiple linear regression with SPSS version 25. Results indicate that: (1) service quality has a positive and significant effect on customer loyalty (t = 19.652; β = 0.648; p = 0.000); (2) price has a positive and significant effect on customer loyalty (t = 5.293; β = 0.202; p = 0.000); (3) customer satisfaction has a positive and significant effect on customer loyalty (t = 12.923; β = 0.435; p = 0.000); and (4) simultaneously, all three variables significantly affect customer loyalty (F = 375.685; p = 0.000; R² = 0.913), meaning 91.3% of the variation in customer loyalty is explained by the model. Service quality is the most dominant variable (β = 0.648). These findings imply that Maxim needs to continuously improve service quality standards, set competitive prices, and ensure customer satisfaction to maintain long-term customer loyalty in the highly competitive online transportation market.